PENGGUNAAN MEDIA FILM ANIMASI JAMAL LAELI UNTUK MENINGKATKAN KETERAMPILAN BERBICARA PADA ANAK KELOMPOK A DI TK NEGERI 2 POTO TANO - Alti Krismayani; Fahruddin; Abdul Kadir Jaelani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The purpose of this study is to improve the speaking skills of group A children in Kindergarten Negeri 2 Poto Tano through the use of Jamal Laeli's animated film media. The type of research used is classroom action research (PTK). The data collection method is observation and documentation with qualitative descriptive data analysis by looking at the learning process and learning outcomes of children's speaking skills. The subjects in this study are group A children at Kindergarten Negeri 2 Poto Tano which totals 16 children. The results of the research on the use of animation film media